Taphonomic analysis of the exceptional preservation of early bird feathers during the early Cretaceous period in Northeast China - Zhao, Yan; Tian, Qian; Ren, Guang-Ying; Guo, Ying; Zheng, Xiao-Ting (Frontiers in Earth Science, 2023)
Fossil soft tissues contain important and irreplaceable information on life evolution, and on the comprehensive understanding of the nature of Mesozoic ecosystems. Compared to other fossil soft tissues, Jehol Biota feathers are more commonly reported. However, taphonomic analysis of these feathers is lacking. Here, five Jehol Biota specimens of early bird Sapeornis chaoyangensis with differently preserved feathers were selected. One specimen, STM 15-36, has a complete set of extraordinarily preserved feathers. An interesting consequence was revealed by their host sediment Zr/Rb analysis that specimen STM 15-36 possesses the coarsest sediment grain size but the best-preserved feathers. More geochemical analyses of host sediments, including organic carbon isotopes and major elements, were conducted to restore the paleoenvironment during those Sapeornis’ burial. The result mainly shows that the paleoclimate when Sapeornis STM 15-36 was buried is warmer and wetter than those of the other four; STM 15-36 host sediment has a pure terrestrial-derived organic input, while the others are aquatic algae. In addition, redox-sensitive trace elements analysis indicates the lake bottom-water preserved Sapeornis STM 15-36 is anoxic and restricted, being more oxygen-depleted than those of the other four. Therefore, the transportation and burial of Sapeornis STM 15-36 were preliminarily inferred as: the carcass of Sapeornis STM 15-36 was transported rapidly into the lake by a short and strong rain flush, and then was buried quickly by the accompanying terrestrial debris; the subsequent anoxic and restricted burial environment inhibited bioturbation and hydrodynamic disturbance on Sapeornis STM 15-36 and its host sediments, allowing its whole set of feathers to be delicately preserved. This finding provides a valuable case study on understanding the taphonomy of fossil soft tissues’ exceptional preservation in Jehol Biota.